Anomalous nonthermal fixed point in a quasi-two-dimensional dipolar Bose gas - Rasch, Niklas; Chomaz, Lauriane; Gasenzer, Thomas (Physical review, 2025)
The emergence of distinctly subdiffusive scaling in the vicinity of an anomalous nonthermal fixed point is discussed in a quasi-two-dimensional dipolar Bose gas in the superfluid phase, carrying ensembles of vortices and antivortices with zero net angular momentum. The observed scaling behavior reflects coarsening dynamics driven by the mutual annihilation of vortices and antivortices, with the mean interdefect distance growing algebraically over time as ℓv⁡(𝑡)∼𝑡𝛽. A subdiffusive (𝛽<12) exponent 𝛽≈0.2 is extracted for various parameter regimes, initial conditions, and dipolar configurations from both scaling occupation-number spectra and the evolution of interdefect distances as well as the corresponding total vortex densities. As vortex-antivortex annihilation progresses, excitations of the background condensate increase. This gives rise to a transition in the scaling behavior at late times, toward a nonthermal fixed point governed by diffusion-type scaling with 𝛽≈12 as expected for the mutual annihilation of well-separated vortex-antivortex dipoles. While the temporal scaling with 𝛽 does not depend significantly on the strength and anisotropy of the dipolar interactions and thus underlines the universality of the anomalous as well as diffusion-type nonthermal fixed points, we find distinctly different vortex patterns resulting in the dipolar case. While in the superfluid with contact interactions only, same-sign vortices tend to cluster and form large-scale eddies, in the dipolar and tilted cases, roton excitations appear to prevent such motion, giving rather rise to a maximization of distances between vortices of either sign.